O sintoma social ou o sintoma com Marx: um conceito psicanalítico - Xavier, Karla Rampim (2013)
In psychoanalytic praxis the symptom is a concept widely worked which intervenes both in clinical practice and the politics of psychoanalysis, meanwhile it is a subject intrinsically linked to the social bond. The symptom is precisely the truth that makes disorder, it is opposition face to mastery discourse. In Freud s theory it seems not to be possible to formalize a symptom as social. However with Lacan such formalization is possible due to the thesis that it was Marx who invented the symptom. To enter this question was necessary to research what is symptom for Lacan, and thereafter ascertain the Lacanian references that trace direct connection between psychoanalysis and Marxist theory, as well as analysis of homology between surplus-jouissance and surplus-value. In this way that it is intended the understanding of Marx as inventor of the symptom. What we see is that a lot has been said about the social symptom, often without the necessary theoretical rigor, but for Lacan there is only a social symptom, "each individual is really a proletarian." But anyway, what does this mean? To conclude, we analyze how controversial and divergent this issue may be. Furthermore, we analyze how the theory of social symptom can be a resource for the psychoanalyst on the issues of bond and polis